PENGARUH HUMAN RELATION DAN LINGKUNGAN KERJA TERHADAP ETOS KERJA KARYAWAN PADA PT. PELABUHAN INDONESIA (PERSERO) REGIONAL I CABANG DUMAI - Haryuni, Sri; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research is focused on the influence of Human Relations and Work Environment on the Work Ethic of employees at PT. Pelabuhan Indonesia (Persero) Regional I Cabang Dumai. The purpose of this study was to determine the effect of human relations and work environment on the work ethic of employees at PT. Pelabuhan Indonesia (Persero) Regional I cabang Dumai. Human relations and work environment as independent variables (X1, X2) while the work ethic of employees as the dependent variable (Y). The problem in this study is the occurrence of fluctuating employee turnover and employee absenteeism which increases every year.seen from the data on Labor Turn Over and company absenteeism. The sample of this study was taken as many as 62 respondents from the population which was calculated using the Slovin formula. The data obtained from the results of the questionnaire and then processed and then tested statistically through the SPSS program. The data analysis techniques used are validity and reliability tests, simple linear analysis and multiple linear analysis, coefficient of determination, t test and F test. Based on the results of the tests conducted, it shows that human relations and work environment have a positive and significant effect on the work ethic of employees at PT. Pelabuhan Indonesia (Persero) Regional I Cabang Dumai. Keywords: Human Relation, Work Environment, And Work Ethic